The Role of Big Data in Improving Educational Management Decisions in Madrasah - Wibowo, Adi; Faridah, Ida; Nurmalasari, Ita (Universitas Nurul Jadid Probolinggo, Indonesia, 2023)
This study aims to explore the role of Big Data in improving educational management decisions in Madrasah. Using a qualitative approach with case studies, the research subjects include educational managers, teaching staff, and students. Data collection techniques consist of observation, interviews, and documentation, while data analysis includes reduction, presentation, and drawing conclusions. The results of the study indicate that the application of Big Data significantly improves educational management decisions through four main indicators: student performance analysis, learning personalization, operational efficiency, and trend prediction. Big data analysis allows management to optimize resource allocation, adjust teaching methods to student needs, and make more accurate data-based decisions. The application of Big Data also helps in identifying educational trends and reducing waste, which ultimately improves the quality of education and operational efficiency. These findings underline the importance of data technology integration in designing more effective and result-oriented educational policies and strategies.